Photoluminesscence and photoacoustic effect of erbium-doped porous silicon nanostructure. - Sekak, K. A.; Abdullah, S.; Paiman , Suriati; Mat Yunus , Wan Mahmood (World Scientific Publishing, 2006)
We applied photoluminescence (PL) and photoacoustic techniques on erbium-doped porous silicon nanostructured (Er-doped-PSN) to study the influences of weight percent (%) of erbium-doped in PSN. Erbium-doped PSN has been intensively studied due their potentiality for optical devices such as waveguide and optical amplifier. Electrochemical technique was used to prepare the PSN samples. Polished p-type [100] c-Si was used as based material. Erbium doping process was carried out by electrodeposition technique using Erbium Chloride (ErCl3) and ethanol composition as electrolyte. The weight percent of Er concentration is varied to get the optimum effect on PL. The doping process improves PL intensity and changing in peak position. Photoluminescence measurements were performed in the visible light range and excited with the 380 nm line a Xenon (Xe) light source. Photoacoustic (PA) measurements is useful to obtain the optical absorption characteristic for strongly scattering media such as PSN and it helps to confirm the possibility of a strong quantum confinement effect.